Culturally based gender bias in science education - Nauman, Ann K. (CIENCIA ergo-sum, 2017)
A study of gender, science, and technology involves bath biological and historical issues. Behavioral differences between women and men have been researched and can be attributed to the historical roots of a culture's altitudes and practices. Through both anthropological and educational research, the author has investigated gender bias, particularly in science and mathematics. Studies in several culturally diverse areas, including parts of Africa, Cuba, and Asia, are an integral part of this research. In addition, women themselves are challenged to question their own views and those altitudes which they readily accept and teach to future generations. The primary purpose of this paper is the investigation of the cultural bases of gender role assignment and the need for addressing and changing cultural altitudes in arder lo provide greater educational equality and opportunities for females.